EFEKTIVITAS KONSELING KELOMPOK DENGAN TEKNIK PENGKONDISIAN AVERSI DALAM MENGATASI PERILAKU ADIKSI - Armey Rolizky; Bela Janare Putra; Suryati Suryati (ScidacPlus, 2023)
One technique in counseling is aversion conditioning, which is used to change emotional responses to harmful or undesirable behavior in behavior therapy. This research uses a one group pre-test post-test design. A pretest was carried out on a group of research subjects, then treatment was given, and followed by a posttest using the same measurements. The method used in the research was observation, documentation and distribution of questionnaires to clients at the Palembang Ar-Rahman Drug Rehabilitation Center Foundation. The calculation results from the pre-test before the treatment was given were 60.53 and after the treatment was given and the post-test was carried out the results were 124.53. So it can be concluded that there has been an increase in the level of self-control of former drug addicts. The conclusion of this research is that before being given group counseling using aversion techniques, clients at the Ar-Rahman Palembang rehabilitation foundation lacked self-control in overcoming addictive behavior. There was an increase in overcoming addictive behavior after being given group counseling with aversion techniques to clients at the Ar-Rahman Palembang rehabilitation foundation. There is a difference in the effectiveness of group counseling and aversion techniques in overcoming addictive behavior. Keywords: Addiction, Group Counseling, Aversion Conditioning Techniques